Silicon and silicide nanowires : applications, fabrication, and properties - Huang, Yu (College teacher); Tu, K. N. 1937- (Pan Stanford Pub., 2013)
This book comprises theoretical and experimental analysis of various properties of silicon nanocrystals, research methods and preparation techniques, and some promising applications. It comprises nine chapters. The first three are based on processing, the next three on properties, and the last three on applications of nanowires of silicon and silicides.